Plant metabolites as potential food preservatives - Quiroga, Emma Nelly (2006)
Inadequate techniques of culture, recollection and storage of food and forages, can lead to fungi development producing toxic chemical compounds. Occurrence of mycotoxins in food causes loss of  the nutritious value, and produces harmful effects on human and animal health. The aims of this study were: (a) To determine the ability to produce aflatoxins in four (4) Aspergillus strains isolated from balanced food used for farm animals. (b) To analyse in vitro fungitoxic effect of alcoholic extracts of Tripodanthus acutifolius and Larrea divaricata, plants used in the popular medicine of Tucumán region (Argentine). Of the four Aspergillus strains isolated from balanced food, only A. nomius VSC23 and A. nomius 13137 showed to be aflatoxigenic strains. From the culture medium where both strains developed, a compound was isolated and identified as Aflatoxin B1 by TLC. These findings were confirmed by isolation of the yellow pigment that changed colour according to pH to which was exposed. The tinctures of T. acutifolius and L. divaricata were selected to carry out this work, according with previous evidence of their antifungal effect. The fungitoxic efficiency of the mentioned extracts was proved by determining MIC values of both extracts, which were compared with the MICs of organic acids (ascorbic acid and sorbic acid) usually used as food preservatives. Quite similar values were obtained between both types of antifungic substances. These results suggest that some metabolites may be isolated from plant species of northwestern Argentine (T. acutifolius and L. divaricata), which could be used to avoid polluting fungi growth, and further synthesis of mycotoxins, thus being useful for food and stored forages conservation.